Analysis Of The Mathematics Textbook For 10th Grade High School Under The Merdeka Curriculum (Revised Edition) On The Topic Of Trigonometry - Lidia Aprilia Tangdilintin; Rifka Adriani Aswar; Aslan Indra Mahananta; Muhammad Ammar Naufal (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to conduct a critical review of the Merdeka Curriculum Grade 10 Mathematics Textbook (Revised Edition 2023) on trigonometric ratios. The study focuses on analyzing the structure of the concept map, the suitability of the material with the learning objectives using the ABCD framework (Audience, Behavior, Condition, Degree), the depth of mathematical essence, the identification of problems in the presentation of material, and the evaluation of the strengths and weaknesses of the textbook. This research uses a qualitative descriptive method with documentation study and content analysis techniques on the textbook as the object of research. The results show that the book presents the material systematically, contextually, and supports active learning through varied exploration and visual representation activities. However, several problems were found, including the lack of a strong connection between prerequisite concepts, the absence of a conceptual bridge between exploration and formal symbolization, a high level of abstraction of concepts without adequate reinforcement of representations, the dominance of high-level cognitive exercises without gradual differentiation, and the presentation of special angle material that tends to be procedural. In addition, the formulation of learning objectives did not fully meet the ABCD components, particularly in terms of conditions and degree of achievement. Therefore, improvements are needed in the conceptual structure, strengthening the transition from concrete to symbolic contexts, providing graded exercises, and formulating more specific and measurable learning objectives to optimally support students' conceptual understanding and problem-solving skills.